Urgensi pendidikan agama islam dalam menjaga moral di era society 5.0 - A'imah, Ziadah Nuril (Maliki Interdisciplinary Journal, 2026)
The era of Society 5.0 introduces significant transformations in human life through the integration of smart technologies and advanced digital systems. However, these developments also trigger various moral crises, including the uncontrolled spread of information, cyberbullying, declining communication ethics, and increasing digital individualism. Within this context, Islamic Religious Education (PAI) holds a critical level of urgency as a foundation for character formation and a moral compass for society. The concept of PAI goes beyond the mere transfer of religious knowledge; it encompasses the processes of tarbiyah, ta’lim, and ta’dib, which emphasize spiritual, intellectual, and ethical development of learners. Through the internalization of monotheistic values, proper conduct, and the balance between faith and science (IMTAQ and IPTEK), PAI provides moral direction amid rapid technological advancement. The urgency of PAI in the Society 5.0 era lies in its role in instilling honesty, responsibility, politeness, and digital ethics, enabling learners to use technology wisely and ethically. Thus, PAI serves as a crucial pillar in maintaining moral stability and ensuring that technological progress remains aligned with humanistic and spiritual values.